Characterization of a bacteriocin of pediococcus pentosaceus SB83 and its potential for vaginal application - Borges, Sandra (2015)
Listeria monocytogenes, the responsible agent for listeriosis, is one of several microorganisms which can be transmitted from mother to fetus/neonate by vertical transmission. The aim of this study was to characterize a bacteriocin produced by Pediococcus pentosaceus SB83 for vaginal application, to prevent colonization of pregnant women with L. monocytogenes. Bacteriocin SB83 showed inhibitory activity against L. monocytogenes (serotypes 1/2a 1/2b and 4b) but did not inhibit vaginal lactic acid bacteria. Additionally, bacteriocin SB83 inhibited the growth of Enterococcus faecalis, Enterococcus faecium and Bacillus subtilis. Bacteriocin SB83 was produced at maximum levels between 24 h and 36 h of growth (6400 AU/mL against serotype 1/2b and 4b, 3200 AU/mL against serotype 1/2a). Significant reduction in antimicrobial activity was observed after treatment of cell-free supernatants with proteinase K, pepsin, papain and trypsin. Bacteriocin SB83 was resistant to treatments with Tween 80, Tween 20, Triton X-100, SDS and EDTA. This bacteriocin was stable at pH values between 4 and 6.5; a decrease in activity was observed at pH 2 and above 8. A decrease in antibacterial activity was recorded at 100 °C and 121 °C. In the range 4 °C to 80 °C, antimicrobial activity was not affected. The activity of bacteriocin did not change in simulated vaginal fluid (pH 4.2, 5.5 and 6.5). The molecular size of bacteriocin SB83 was between 3.5 and 6.5 kDa.In conclusion, the bacteriocin produced by P. pentosaceus SB83 has been proved to be resistant to several conditions, including conditions in the vaginal tract (pH and components of vaginal fluid).